(3TQM eNJUQ CHj LYaQ GdWMGhis - (3CMeO Hf Ydj GdnqQGRj, CHh HcQ GdLUGU,J (B370 (3g` s; (3CMeO Hf eMeO Hf SdGeI Hf SdeI GdCROqj GdWMGhj, CHh LYaQ,J (B321 (3g` s ((3GdYdGeI GdEJbGfi s)
(3ChdgG (B:s
(3CKfGA SaQ CHj SajGf Edi JdeOjfI jTgO GdYgO s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3GdLRA GdCNjQ efgs
(3GdfSNI HgG MhGTs
(3ecJhH HNWhW eNJdaI CNQgG NW GdGJbGfi SfI (B748s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs